Issues arising from social media and their Quranic solutions: سوشل میڈیا سے پیدا ہونے والےمسائل اور ان کاقرآنی حل - Bano, Dr. Saeeda; Munawer, Shiza; Fatima, Alvia (Al Khadim Research Journal of Islamic Culture and Civilization, 2025)
In today’s modern era, where man has reached space from the earth with new inventions, man has also been able to hold the entire world in his hand through a modern invention. Through mobile phones and the Internet, man has also been connected to social media, through which man has been able to convey his ideas and thoughts to other people. He has also started to preach his religion and reform others through it in a modern way. But where one thing has immense positive effects, similarly, it also has a sea of ​​hidden negative effects, which instead of taking man on the path of progress, it keeps on putting him in decline. But by aligning social media usage with Quranic ethics, users can mitigate harm and promote a culture of respect, integrity and spiritual mindfulness.